Perfil clínico epidemiológico y laboratorial en pacientes diabéticos adultos con crisis hiperglicémicas - Pumamango Córdova, Jimmy Emerson (2017)
Determine the clinical, epidemiological and laboratory profile of adult diabetic patients with hyperglycemic crisis treated in the emergency department and hospitalization of Internal Medicine of Hospital Belén de Trujillo from January 2004 to December 2014. Material and method: The present study fits a type of observational, descriptive and retrospective study; whose population consisted of 500 medical records, with a sample of 134, selected at random considering the exclusion and inclusion criteria. outcomes: The most frequent type of Hyperglycemic Crisis was Diabetic Ketoacidosis, followed by Hyperglycemic Hyperosmolar State; Were also frequent: The female sex, living in Districts of Porvenir and Florencia de Mora; Having housewife or non-working occupation; Being in the sixth decade of life; history of Type 2 Diabetes Mellitus (DM); The Alert State upon entry; Symptoms such as polydipsia, dehydration and fatigue; Urinary tract infection as the cause; And be alive as a condition of discharge. The mean values for CAD were pH 7.17, bicarbonate 7.1 mmol/L, osmolarity of 304 mOsm/L, blood glucose of 579.16 mg/dl. For the hyperglycemic hyperosmolar state were pH 7.44, osmolarity of 331.12mOsm/L, blood glucose at 871,654mg/dL. Conclusion: The profile found in our locality shows concordant part with the described in the Theory, as well as non concordant part with the same